Current trends in nitric oxide research - Ray, A.; Chakraborti, A.; Gulati, K. (Cellular and Molecular Biology, 2007)
Nitric oxide (NO), a molecule with multidimensional effects has generated exponential amount of research since its identification as a biological messenger almost two decades back. The recent trend in NO research is to explore newer dimensions in the cellular and molecular mechanisms of actions and interactions of NO with various biomolecules and their implications in various pathophysiological states. Advances in our knowledge of the mechanisms by which this pleiotropic molecule regulates the expression of eukaryotic genes has generated considerable excitement and is paving the way for development of novel NO based therapeutic strategies. However, it is still a challenge to understand fully the paradox of beneficial and damaging effects of this exciting molecule. This review will discuss the current trends of research in this area especially highlighting the new insights gained from recent experimental and clinical studies. New approaches to reduce or augment the availability of NO to benefit a wide range of clinical conditions and avenues for future research are also briefly discussed.